King Oyster Mushroom, Pleurotus eryngii (Agaricomycetes), Extract Can Attenuate Doxorubicin-Induced Lung Damage by Inhibiting Oxidative Stress in Rats - Tektemur, Nalan Kaya; Tektemur, Ahmet; Guzel, Elif Erdem (Begell House Inc, 2023)
Doxorubicin (DOX), a broad spectrum chemotherapeutic, has toxic effects on healthy tissues. Mitochon-drial processes and oxidative stress act in the DOX-induced toxicity, therefore antioxidant therapies are widely used. The study was aimed to evaluate the therapeutic potential of Pleurotus eryngii extract (PEE), an extract of a fungus with antioxidant properties, against DOX-induced lung damage. Rats were divided into Control, DOX, DOX + PEE, and PEE groups (n = 6). DOX was administered intraperitoneally in a single dose (10 mg/kg BW) and PE (200 mg/kg BW) was administered by oral gavage every other day for 21 days. Histopathological evaluations, immunohistochemical analyses, total oxidant status (TOS)/total antioxidant status (TAS) method, and quantitative real-time polymerase chain reaction (qRT-PCR) analysis were performed. DOX led to severe histopathological disruptions in rat lungs. Also, DOX remarkably increased the expression of dynamin 1 like (DRP1) and decreased the expression of mitofusin 1 (MFN1) and mitofusin 2 (MFN2) genes, which are related to mitochondrial dynamics. Moreover, DOX caused an increase in TOS/ TAS and 8-hydroxy-2-deoxyguanosine (8-OHdG) levels. On the other hand, PEE treatment remarkably normalized the histopathological findings, mitochondrial dynamics-related gene expressions, markers of oxidative stress, and DNA damage. The present study signs out that PEE can ameliorate the DOX-mediated lung toxicity and the antioxidant mech-anism associated with mitochondrial dynamics can have a role in this potent therapeutic effect.
Keywords: drug toxicity; Pleurotus eryngii extract; lung; mitochondria; oxidative damage; medicinal mushrooms